2007
DOI: 10.1586/14737175.7.11s.s35
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclature and endocrinology of menopause and perimenopause

Abstract: The early and late perimenopausal transition is characterized by changing cycle length as well as by menopausal symptoms in some women, including increasing hot flashes and night sweats. Breast tenderness decreases as women enter the late transition. This review, as part of the clinical reviews on the menopausal woman with comorbidity, covers the endocrine phenomena of perimenopause, terminology and the observed clinical characteristics of the transition. It should be noted that the definitions covering this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 32 publications
0
35
0
4
Order By: Relevance
“…As a result of a longitudinal prospective study, Freeman et al 12 reported that the risk of HFs increased throughout the menopausal transition and was greatest in postmenopausal women (odds ratio [OR] 2.87, 95% confidence interval [CI] 1.76-4.67, p < 0.001). In addition, VMS were most strongly related to the late menopausal transition stage in all racial=ethnic groups 10,14,16,17 and nearly as strongly related to postmenopause, even after adjusting for covariates, 10,12,[18][19][20][21][22] as reported in several other published cross-sectional, 10,[16][17][18]20,22 longitudinal prospective, 12,21 and review 14,19 23 Therefore, when performing analysis on factors that affect the incidence or severity of HFs, the nomenclature of the menopausal stages should be introduced along with other covariates in the final multivariate analysis. In summary, the menopausal stages (mainly the menopausal transition and postmenopause) are strongly associated with HFs, but there is still no single menopausal stage that has been identified as the critical time point for experiencing HFs.…”
Section: The Menopausal Stagesmentioning
confidence: 85%
See 1 more Smart Citation
“…As a result of a longitudinal prospective study, Freeman et al 12 reported that the risk of HFs increased throughout the menopausal transition and was greatest in postmenopausal women (odds ratio [OR] 2.87, 95% confidence interval [CI] 1.76-4.67, p < 0.001). In addition, VMS were most strongly related to the late menopausal transition stage in all racial=ethnic groups 10,14,16,17 and nearly as strongly related to postmenopause, even after adjusting for covariates, 10,12,[18][19][20][21][22] as reported in several other published cross-sectional, 10,[16][17][18]20,22 longitudinal prospective, 12,21 and review 14,19 23 Therefore, when performing analysis on factors that affect the incidence or severity of HFs, the nomenclature of the menopausal stages should be introduced along with other covariates in the final multivariate analysis. In summary, the menopausal stages (mainly the menopausal transition and postmenopause) are strongly associated with HFs, but there is still no single menopausal stage that has been identified as the critical time point for experiencing HFs.…”
Section: The Menopausal Stagesmentioning
confidence: 85%
“…Therefore, in 2001, the Stages of Reproductive Aging Workshop (STRAW) proposed conventional terminology for menopause stages. Later, the ReSTAGE Collaboration added supplementary definitions to reproductive aging, 14 thus allowing a comparable distinction between reproductive aging and general aging events. Burger et al…”
Section: The Menopausal Stagesmentioning
confidence: 99%
“…Menopause is a process of normal aging, during which the level of estradiol secreted by the ovaries gradually declines, and menopausal women therefore have irregular menses and much higher incidences of physiological and mental changes, which severely disrupt their quality of life (Burger et al, 2007). The solution to overcome menopausal symptoms seems simple-hormone replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The central and peripheral hormonal changes in menopausal transition and perimenopause were assessed in many research centers from Western Europe [37], Australia [24,38], North America [25], and besides these, the rat models on gene expression analyses demonstrated that there are two distinct aging programs: chronological and endocrine, regarding bioenergetic gene expression involved in brain metabolism and synaptic plasticity [39].…”
Section: Hormonal and Genetic Data On Perimenopausal Neuroagingmentioning
confidence: 99%